Clinical reliability of zirconium abutment in implant restorations in the English and Korean literature - Su-Been Yu; Bong-Gyu Song; Kyeong-Jun Cheon; Ju-Won Kim; Young-Hee Kim; Byoung-Eun Yang (SpringerOpen, 2018)
Abstract Background This study aimed to evaluate the mechanical, biological, and esthetic stability of a zirconium abutment according to evidence-based dentistry. Main text An electronic search was performed. Domestic studies were found using the keywords "zirconia abutments" and "zirconium abutment" in KMbase, KoreaMed, and the National Assembly Library, and international studies were found using the same keywords in PubMed. All identified studies were divided by evidence level from the viewpoint of the research type utilizing the evidence-based review manual. A total of 102 domestic studies (with Korean language) were found, and 9 of these studies were selected. In these nine studies, 3 had evidence level 3 and 6 had evidence level 4. A total of 97 international studies (with English language) were found, and 19 were selected. Among these 19 studies, 5 had evidence level 2 and 7 had evidence level 3, whereas the remainder had evidence level 4. According to the studies, zirconium abutments are mechanically, biologically, and esthetically stable, but the evidence level of these studies is low, and the follow-up duration is no longer than 5 years. Conclusions All examined studies verified the mechanical stability of zirconium abutments for a period no longer than 5 years. Therefore, a long-term clinical observation is needed. Zirconium abutments are thought to be biologically stable, but they are not superior to titanium abutments. As the esthetic stability of such abutments had a low evidence level in the studies that examined here, a much higher evidence level is needed.